Retention in a public healthcare system with free access to treatment: a Danish nationwide HIV cohort study - Helleberg, Marie; Engsig, Frederik N; Kronborg, Gitte; Larsen, Carsten S; Pedersen, Gitte; Pedersen, Court; Gerstoft, Jan; Obel, Niels (AIDS (London), 2012)
We aimed to assess retention of HIV-infected individuals in the Danish healthcare system over a 15-year period. Loss to follow-up (LTFU) was defined as 365 days without contact to the HIV care system. Data were obtained from the nationwide Danish HIV Cohort study, The Danish National Hospital Registry and The Danish Civil Registration System. Incidence rates, risk factors for LTFU and return to care and mortality rate ratios (MRRs) were estimated using Poisson regression analyses. We included 4745 HIV patients who were followed for 36,692 person-years. Patients were retained in care 95.0% of person-years under observation, increasing to 98.1% after initiation of highly active antiretroviral treatment (HAART). The overall incidence rate/100 person-years for first episode of LTFU was 2.6 [95% confidence interval (CI) 2.5-2.8] and was significantly lower after initiation of HAART [1.2 (95% CI 1.0-1.3)]. Five years after LTFU the probability of return to care was 0.87 (95% CI 0.84-0.90). The risk of death was significantly increased after LTFU [MRR 1.9 (95% CI 1.6-2.6)] and 6 months or less after return to care [MRR 10.9 (95% CI 5.9-19.9)]. Retention in care of Danish HIV patients is high, especially after initiation of HAART. Absence from HIV care is associated with increased mortality. We conclude that high rates of retention can be achieved in a healthcare system with free access to treatment and is associated with a favorable outcome.